Modelization of the Personal Learning Environment in the Moroccan Higher Education - Chrifi Ibtissam; Tace Elmostafa; Radid Mohamed; Yazza Younes (Iraqi Journal of Science, 2021)
Any research focusing on the teaching-learning process must focus on the learner, by mobilizing the various devices to facilitate and optimize learning. In this context, we introduce the integration of educational technologies into a personal learning environment (PLE). The PLE has significant potential for learning; namely self-construction and self-management of knowledge. According to Attwel (2007b), the development and improvement of PLE will lead to drastic changes in the way we use educational technology, as well as in the organization and ethics of education. With the present contribution, we try to modelize the PLE of students within institutions of higher education in Morocco. Based on data from a questionnaire put online using google forms, we have found that digital devices are ubiquitous in the daily lives of learners, but their practices are limited to distracting uses, and that the institutional framework remains more basic to manage their learning. The purpose of this study is to develop learning autonomy and to improve the way of using technologies through our student’s conception of the PLE.